Shipping Operation Diagram (SOD) Method in Setting The Departure and Arrival Hours of Trucks at PT ABC - Sabtian, Eko; Ginanjar, Feri Usman; Putri, Alivia; Fauzi, Muchammad (Institut Ilmu Sosial dan Manajemen Stiami, 2022)
PT. ABC is a company engaged in the plastic manufacturing industry that produces a wide range of products, from automotive plastics, cosmetic plastics, houseware plastics, health plastics to plastics for pharmaceutical purposes. Meeting customer needs in a timely manner is necessary so that customers have satisfaction with company services. The problems experienced by PT ABC. is the arrangement in scheduling automatic product delivery to customers. This research is aimed at using the Shipping Opertaion Diagram method in determining the hours of departure and arrival of trucks by considering the pulling time of late delivery and visualizing delivery information to make it right on target. The results of this study are expected to be able to adjust the departure time for delivery of goods based on product storage.